Promoting Metacognitive Decision-Making in Teacher Education. Issue 3 (2nd July 2016) - Griffith, Robin; Bauml, Michelle; Quebec-Fuentes, Sarah
Abstract : Effective teachers are characterized by their abilities to make thoughtful, deliberate, and informed adaptations while teaching (Hoffman & Pearson, 2000). These in-the-moment teaching decisions are guided by a complex web of teacher knowledge. Raising teachers' awareness of the decisions they make on a moment-by-moment basis may aid in thoughtful, more deliberate decision-making and more robust instruction. We charge that preservice teachers can acquire this skill, as well. This article highlights practices employed in preservice teacher education courses as a means to promote awareness of, and engagement with, in-the-moment teaching decisions. Using examples from mathematics, social studies, and literacy methods courses, we describe our processes to intentionally cultivate preservice teachers' adaptive teaching skills through metacognitive decision-making.